Finite-length network coding for multi-hop video streaming in vehicular networks - Surathi Srikiran Rao (2018)
Providing high quality video streaming over multi-hop vehicular networks is a challenging problem because the inter-vehicular channels are noisy, error prone and time varying. A finite-length network coding technique, called Batched Sparse (BATS) Code, can recover packet errors and improve the delivery rate for multi-hop communications. However, the traditional BATS code was designed for quasi-static channel, where the end-to-end channel quality can be well estimated. In this project, extensive experiments with commercial modems have been conducted to characterize the packet reception probabilities of Vehicular-to-vehicular (V2V) communications with various modulation coding schemes and communication distances. Based on the measured results, we optimize the degree distribution of the BATS code so that it matches well with the channel. The optimized BATS code is then applied for achieving real-time video streaming over the NTU-NXP Smart Mobility Testbed.